PENERAPAN METODE VALUE FOR MONEY SEBAGAI TOLOK UKUR PENILAIAN KINERJA KEUANGAN PADA ORGANISASI SEKTOR PUBLIK DI DINAS KESEHATAN KOTA MANADO - Wuwungan, Gabriela Thalia; Tinangon, Jantje; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2019)
In this era of globalization, many people consider the financial sector of public sector organizations as a waste and a source of funding. Loss of public trust in lost public sector organizations. In addition, accountability reports on public sector organizations are only oriented to